Colorectal cancer screening and subsequent incidence of colorectal cancer: results from the 45 and Up Study. Issue 9 (3rd November 2014) - Steffen, Annika; Weber, Marianne F; Roder, David M; Banks, Emily
Abstract: Objective: To investigate the association of colorectal cancer (CRC) screening history and subsequent incidence of CRC in New South Wales, Australia. Design, setting and participants: A total of 196 464 people from NSW recruited to the 45 and Up Study, a large Australian population‐based prospective study, by completing a baseline questionnaire distributed from January 2006 to December 2008. Individuals without pre‐existing cancer were followed for a mean of 3.78 years (SD, 0.92 years) through linkage to population health datasets. Main outcome measures: Incidence of CRC; hazard ratio (HR) according to screening history, adjusted for age, sex, body mass index, income, education, remoteness, family history, aspirin use, smoking, diabetes, alcohol use, physical activity and dietary factors. Results: Overall, 1096 cases of incident CRC accrued (454 proximal colon, 240 distal colon, 349 rectal and 53 unspecified cancers). Ever having undergone CRC screening before baseline was associated with a 44% reduced risk of developing CRC during follow‐up (HR, 0.56; 95% CI, 0.49–0.63) compared with never having undergone screening. This effect was more pronounced for those reporting endoscopy (HR, 0.50; 95% CI, 0.43–0.58) than those reporting faecal occult blood testing (FOBT) (HR, 0.61; 95% CI, 0.52–0.72). Associations for all screening exposures were strongest for rectal cancer (HR, 0.35; 95% CI, 0.27–0.45) followed by distal colon cancer (HR, 0.60; 95% CI, 0.46–0.78), while relationships were weaker for cancers of the proximal colon (HR, 0.76; 95% CI, 0.62–0.92). Conclusion: CRC incidence is lower among individuals with a history of CRC screening, through either FOBT or endoscopy, compared with individuals who have never had CRC screening, lasting for at least 4 years after screening.